Creation and validation of the Chinese regulatory focus in relationships scale across multiple relationships context - Li, WeiWei; He, XiaoQi; Wang, Yun; Zeng, XiHua (Frontiers in Psychology, 2022)
A regulatory focus in relationships motivates individuals to be concerned about the presence/absence of positives (promotion focus)/negatives (prevention focus) in social interactions. How to capture specific patterns and meanings of regulatory focus in relationships remains unclear. Based on regulatory focus theory, we created a regulatory focus in relationships scale (RFRS) with a sample of Chinese undergraduates. The RFRS included four subscales of interpersonal relationships (parent-child, teacher-student, friend, classmate), each of which consists of a model of promotion-prevention focus. With a series of interviews and tests, we found that the RFRS had acceptable validation and reliability. And promotion-prevention focus in relationships is context-dependent: Chinese undergraduates hold high promotion and low prevention focus for parents, friends, and classmates, while they hold high prevention focus and low promotion focus for teachers. The regulatory focuses in relationships newly created can be used for future studies to test relational motivation in the specific interpersonal context.